Potensi dan Keragaman Bakteri Endofit sebagai Agens Pemacu Pertumbuhan dan Biokontrol Anggrek - Mery Irianti Amba Linggi; Tri Joko; Jaka Widada (Jurnal Ilmu Pertanian Indonesia, 2023)
Soft rot disease in orchid plants is a factor in decreasing orchid production. One way of biological control that has the potential to spur growth is to utilize endophytic bacteria. This study aims to describe the diversity of orchid endophytic bacteria that have the potential as growth promoters and biocontrol agents. Observation parameters include indole acetic acid (IAA) production, inorganic phosphate dissolution, ammonia production of orchid endophytic bacteria, and antagonism of endophytic bacteria to pathogenic bacteria that cause soft rot in vitro. The diversity of orchid endophytic bacteria was analyzed using rep-PCR with BOX-A1R primer. The results showed that 10 isolates of orchid endophytic bacteria were able to produce IAA with a concentration of 79–321 μg/mL, able to dissolve phosphate, and produce ammonia. In antagonism testing against soft rot-causing bacteria, all isolates were able to form an inhibitory zone with a diameter of 3–7.2 cm. Furthermore, diversity analysis using rep-PCR showed that isolates of endophytic bacteria DnPh5, BgCt2, BgVt10, DnLp7, DnBl1, and DnAr4 had a uniform DNA band pattern so that they were grouped together. Meanwhile, isolates of TbPh7, IbtPhm1, DnDr2, and AkOc1 showed different DNA band patterns, indicating that the four isolates were different species or subspecies of bacteria. In dendrogram analysis, DnPh5, BgCt2, BgVt10, DnLp7, DnBl1, and DnAr4 isolates have a similarity of 100%. The similarity of isolates IbtPhm1, DnDr2, and AkOc1 was 90%, 79%, and 68%, respectively, against the other six isolates. TbPh7 isolate is an isolate with a low level of similarity to other isolates, which is about 51%. Keywords: orchid, endophytic bacteria, growth promoter, biocontrol agent, rep-PCR